Reflections on the preservation and conservation of sacred vestments in Brazil: technical, historical, and museological aspects - Moreira, Fuviane Galdino (2025)
Proposal and Synthesis of Dossier 17: "The Musealization and Conservation of Textile Collections: Sacred Art and Clothing"